Strategi Komunikasi Pemasaran Karya Musik dalam Mempertahankan Popularitas O.M Adella - Indri Novita Sari, Indri; Gilang Gusti Aji (Universitas Negeri Surabaya, 2025)
This study analyzes O.M Adella’s marketing communication strategy in maintaining its popularity in the digital music industry. Using a descriptive qualitative approach, the research explores the use of social media platforms such as YouTube, TikTok, and Instagram as primary promotional tools, as well as branding strategies through fan communities and merchandise sales. Data were collected through interviews, field observations, and document analysis. The findings indicate that digital marketing effectively enhances brand awareness through innovative content and collaborations with renowned songwriters. Organized fan community management and digital promotions support sustainable market expansion. These findings provide insights for the music industry on optimizing digital media to maintain market relevance and industry presence.